Analysis of Solid Medical Waste Management at the Johan Pahlawan Health Center, West Aceh Regency - Nurul Azmi; Darmawi Darmawi (RADJA PUBLIKA, 2022)
Community Health Center is one of the functional health service units in which there are activities that produce medical and non-medical waste in the form of solid and liquid. Solid medical waste is the final waste generated from hospital activities or health services consisting of infectious waste, pathological waste, sharp object waste, pharmaceutical waste, cytotoxic waste, chemical waste, radioactive waste. Solid medical waste that is not managed properly on the environment can cause environmental pollution of health facilities and the spread of germs that continue to grow through air, water, floors, food, and medical and non-medical equipment. Based on data from the Aceh Barat District Health Office, there are 14 health care facilities, of which 13 health centers (inpatient and non-inpatient) and 1 hospital. In the District of Johan Pahlawan there are Puskesmas A and Puskesmas B, but the researchers conducted research in 1 puskesmas. In this study, the method used is a qualitative method with a descriptive approach, namely through observation and in-depth interviews. The purpose of this study was to find out how to manage solid medical waste at the Puskesmas in the District of Johan Pahlawan.